The Outpatient Approach to Dizziness - Brune, Anthony J.; Eggenberger, Eric R. (Seminars in Neurology, 2021)
The evaluation of the dizzy patient is complicated by many common pitfalls. The patient's description of symptoms and the standard neurologic examination are often nonspecific or unrevealing, and neuroimaging is most often normal. Over the past several years, research has demonstrated that a refocusing of history taking results in more reliable and diagnostically helpful information. This can guide a targeted expansion of the exam, often with an emphasis on eye movements.
Keywords: vertigo; vestibular; dizziness